Modifiable Factors Associated with Uncontrolled Type 2 Diabetes Mellitus: Experience in a Tertiary Care Hospital of Bangladesh - Khoda, Mohammad Mehfuz E; Shimu, Ishrat Jahan; Mitra, Palash; Hossain, Md Jakir; Sarkar, MA Sattar; Saha, Anup Kumar; Alam, Md Billal (BIRDEM Medical Journal, 2018)
Background: Diabetes mellitus is a non-communicable disease with increasing prevalence worldwide. The present study was done to identify the modifiable factors that were associated with the poor glycemic control in Bangladeshi type 2 diabetic patients attending in a tertiary care hospital. Methods: This cross-sectional study was conducted in the Department of Medicine, Sir Salimullah Medical College & Mitford Hospital (SSMC & MH), Dhaka from July 2014 to June 2015. A total of 140 adult type 2 diabetes mellitus patients were included in this study. Of them 70 patients had uncontrolled diabetes mellitus with glycated haemoglobin ³ 7% (group 1) and 70 patients with controlled diabetes mellitus (HbA1c< 7%) (group 2). Results: The present study demonstrated statistically significant difference regarding the mean age of both group 1 and group 2 [59.26±12.88 years and 55.24±11.52 years respectively (p <0.05)] and mean duration of diabetes [10.44±8.46 years and 5.96±6.39 years (p=0.0006) respectively]. Moderate physical activity was significantly (p=0.018) associated with good glycaemic control (group 1= 15.7% and group 2= 32.9%). Mean body mass index (BMI) of both group 1 and group 2 were almost equal (23.73±4.72 Kg/ m2 and 23.87±4.86 Kg/ m2 respectively) with no statistical significance and waist hip ratio was 0.98±0.07 and 0.95±0.09 respectively which was statistically significant (p=0.013). Poor economic conditions were significantly associated with uncontrolled blood glucose (p <0.05). Poor glycemic control was also significantly associated with smoking (p=0.00038) and frequent visit with specialist physician (p=0.011). Proper counseling was frequently associated with poor glycaemic control. Most of the patients in group 1 were irregular in dietary habit (58.6%) and exercise (67.1%) and intake of refined sugar (60%) were major contributory factors of poor glycaemic control. Conclusions: Low socioeconomic condition, smoking and intake of refined sugar were the significant modifiable factors that contributed to poor glycaemic control of diabetes. Irregular dietary habits and exercise and proper follow up with specialist physician were more frequent with poor blood glucose control. Proper counseling about diabetes and its management was another modifiable factor. Central obesity and longer duration of diabetes were predisposed to uncontrolled diabetes. Birdem Med J 2018; 8(3): 229-234